Evaluation of adverse drug reactions in a tertiary care hospital in India - James, Janet M.; Paul, Eldho M.; Varghese, Dinu; John, Jibin; Kuriakose, Alan; Pillai, Abhirami B.; Pramoj, Shilpa; Chand O., Aparna (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Adverse drug reaction (ADR) is a major concern in the healthcare system and has been a persistent issue in the health sector. This study aimed to evaluate and assess the ADRs reported, the system organ class (SOC) affected, seriousness, outcomes, causality. Methods: A retrospective observational study in a tertiary care hospital from April 2021 to May 2024. A descriptive analysis of reactions, causality of suspected drugs was carried out according to the setting analysed. Results: Out of 7,396 individual case safety report (ICSR) reported, the highest number of ADRS was reported in the age group of 18-65 years (57.8%) and male patients (51.1%). Using World Health Organization-Uppsala Monitoring Centre (WHO-UMC) causality assessment scale, 67.1% events were possible. A significant majority of drug reported as ‘certain’ were of anti-infective class (51.03%). Most frequently affected SOC was blood and lymphatic system disorders (15.9%), Of all events, greater part of the reactions was non-serious (95.3%), the most drugs causing ADRs was anti neoplastic and immunodulating agents (40.4%) and 47.2% of drugs were high alert medications. The greater part of ADRs reporting was carried out by clinical pharmacists (95.9%). Conclusions: The results highlighted the importance of clinical pharmacist in monitoring and spontaneous reporting of ADRs. Awareness and educational programs may help in active reporting among all healthcare providers.